Holy Sites, Archaeological Monuments and the Perennial Contest over Material Heritage - Rountree, Kathryn (2015)
The article examines several cases of contested sites, situating the sometimes fraught relationship between proponents of religion and archaeology-with their competing claims to authority and 'truth'-within the longstanding contest between Religion and Science. In particular the article addresses cases where sites in Greece (classical temples), Ireland (the Hill of Tara), Britain (Avebury, Stonehenge, the Rollright Stones) and Estonia have been contested by archaeologists and modern Pagans. Such contests begin with the ways in which places are named and discursively framed ('holy' or 'sacred place' versus 'archaeological site'), which in turn have material consequences for what happens at sites: how they are presented, represented, preserved, experienced and made available for different kinds of use by different kinds of people. The paper shows that archaeologists and Pagans are not always on opposite sides. Given that the State frequently has the ultimate power to determine what happens at heritage sites, Pagans' alignments or negotiations with State agendas in relation to sites can make a difference to their ability to contribute to sites' meanings, management, protection and use.
Keywords: contestation of ancient sites; Excavations (archaeology); Heritage; Historic sites; Modern Pagans; Monuments; Neopagans; RELIGION & science; religion and archaeology; State's power